Chinese Herbal Preparation SaiLuoTong Alleviates Brain Ischemia via Nrf2 Antioxidation Pathway-Dependent Cerebral Microvascular Protection - Xiao-Di Fan; Xiao-Di Fan; Ming-Jiang Yao; Ming-Jiang Yao; Bin Yang; Xiao Han; Xiao Han; Ye-Hao Zhang; Ye-Hao Zhang; Guang-Rui Wang; Guang-Rui Wang; Peng Li; et al. (Frontiers Media S.A., 2021)
Stroke is one of the most devastating diseases worldwide. The Chinese herbal preparation SaiLuoTong (SLT) capsule showed outstanding therapeutic effects on stroke and its sequelae. The aim of this study was to further elucidate its therapeutic mechanism. We duplicated a permanent cerebral ischemia model in rats by MCAO and used SLT (33 and 16.5 mg/kg) to intervene. The results showed SLT dose dependently decreased infarction volumes, relieved neuron degeneration and loss, and ameliorated neurological functions, and the dose of 33 mg/kg had statistical significance (compared with the model group, p < 0.05); SLT of 33 mg/kg also significantly inhibited the elevation in brain water content and the loss in claudin-1 and occludin expressions; additionally, it significantly increased nucleus translocation of Nrf2, elevated the expression of HO-1, and raised the activity of SOD and content of GSH (compared with the model group, p < 0.05 or 0.01). These results testified SLT's anti-brain ischemia effect and hint this effect may be related to the protection of brain microvascular endothelial cells (BMECs) that is dependent on the Nrf2 pathway. To further testify, we cultured hCMEC/D3 cells, duplicated OGD/R model to simulate ischemia, and used SLT (3.125, 6.25, and 12.5 mg/L) to treat. SLT dose dependently and significantly inhibited the drop in cell viabilities, and activated the Nrf2 pathway by facilitating Nrf2 nucleus translocation, and increasing HO-1 expression, SOD activity, and GSH content (compared with the model group, p < 0.05 or 0.01); last, the anti-OGD/R effects of SLT, including raising cell viabilities, inhibiting the elevation in dextran permeability, and preserving expressions of claudin-1 and occludin, were all abolished by Nrf2 siRNA interference. The in vitro experiment undoubtedly confirmed the direct protective effect of SLT on BMECs and the obligatory role of the Nrf2 pathway in it. Collectively, data of this study suggest that SLT's therapeutic effect on brain ischemia is related to its Nrf2-dependent BMECs protection.